2014
DOI: 10.1080/14786419.2014.980244
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant phytochemicals in leaf extracts ofBergenia ligulata: a Himalayan herb of medicinal value

Abstract: Phenolic and flavonoid contents in leaf extracts of Bergenia ligulata have been analysed for their contribution in antimicrobial and antioxidant activities. The extracts were prepared in three solvents (separately) following maceration and soxhelt methods. The antimicrobial activity was tested using disc diffusion assay against a range of microorganisms along with the determination of minimum inhibitory concentration (MIC), while the antioxidant activity was tested following DPPH assay. Leaf extracts exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The circumstance that the various microbial isolates subjected to the extract of Bergenia ligulata were susceptible shows that the leaves of this plant have antimicrobial potency. The results were approved with the work of [19], who reported that the leave extract of Bergenia ligulata has antimicrobial and antioxidant potential against some selected range pathogens and infectious diseases. The results obtained show that the ethanolic extracts possess maximum potential against the extract on all microorganisms tested than the aqueous extracts.…”
Section: Discussionsupporting
confidence: 58%
“…The circumstance that the various microbial isolates subjected to the extract of Bergenia ligulata were susceptible shows that the leaves of this plant have antimicrobial potency. The results were approved with the work of [19], who reported that the leave extract of Bergenia ligulata has antimicrobial and antioxidant potential against some selected range pathogens and infectious diseases. The results obtained show that the ethanolic extracts possess maximum potential against the extract on all microorganisms tested than the aqueous extracts.…”
Section: Discussionsupporting
confidence: 58%
“…Among all, three main compounds viz., bergenin catechin and gallic acid are the most sought after compounds of the plant species 30 . During the past years, efforts have been made for identification and quantification of the major bioactive compounds from Bergenia spp 5, 28, 30, 31, 32. However, till date, B. ciliata plant of the Sikkim Himalaya has never been analyzed for secondary metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Citronellol (3,7-dimethyl-6-octen-1-ol) is a linear monoterpene alcohol naturally found in about 70 essential oils, with abundance in Cymbopogon nardus (L.) and citrus oil [124,125]. Cymbopogon nardus was previously used in Chinese medicine to treat rheumatism, fever, and digestive problems [126].…”
Section: Citronellolmentioning
confidence: 99%
“…The constituents have been categorized into polyphenols, flavonoids, quinones, sterols, terpenes, tannins, lactones, and others [16,26,[64][65][66][67]. The major bioactive compounds are bergenin ( 1), (+)-catechin (2), gallic acid (3), β-sitosterol (4), catechin-7-O-β-d-glucoside ( 5), (+)-afzelechin (6), arbutin (10),4-O-galloylbergenin (12), 11-O-galloylbergenin (13), caffeoylquinic acid (21), pashaanolactone (26), 3,11-di-O-galloylbergenin (64), bergapten (66), kaempferol-3-O-rutinoside (70), quercetin-3-O-rutinoside ( 79), (+)-catechin-3-O-gallate (83), 2-O-caffeoylarbutin (86), leucocyanidin (124), methyl gallate (gallicin) (125), sitoinoside I ( 126), β-sitosterol-d-glucoside (127), avicularin (128), reynoutrin (129), procyanidin B1 (135), afzelin (140), and aloe-emodin (146).…”
Section: Acknowledgmentsmentioning
confidence: 99%